3-D rolling car driven by shape memory alloy - Ong, Wei Ming. (2013)
Shape Memory Alloy (SMA) is a material that remembers its original shape and will return to its initial shape when the alloy is heated above certain transition temperature. It was first discovered by Arne Olande in 1938. Despite of the long discovery of SMA since 1930s, its application among all industries is still minor.